2010
DOI: 10.1002/lary.20812
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after middle turbinate resection: Revisiting a controversial topic

Abstract: OBJECTIVE-To evaluate differences in endoscopy exam, olfactory function, and quality-of-life (QOL) status after endoscopic sinus surgery (ESS) for patients with and without bilateral middle turbinate (BMT) resection.STUDY DESIGN-Open, prospective, multi-institutional cohort SUBJECTS and METHODS-Subjects completing enrollment interviews, computed tomography, and endoscopy exam were asked to provide pre-and postoperative responses to the Smell Identification Test (SIT), Rhinosinusitis Disability Index (RSDI), Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
2
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(111 citation statements)
references
References 27 publications
6
95
2
7
Order By: Relevance
“…Soler et al 1184 found that although MT resection was associated with improved endoscopy scores vs MT preservation, there was no difference in RSDI, CSS, and SF-36 scores in CRS patients with or without NP. Importantly, in both nonrandomized cohorts, MT resection was associated with greater disease burden preoperatively, assessed by endoscopy, CT, olfaction testing, and symptom surveys.…”
Section: Xd3 Surgical Principles/techniques-mt Preservation or Resmentioning
confidence: 99%
See 1 more Smart Citation
“…Soler et al 1184 found that although MT resection was associated with improved endoscopy scores vs MT preservation, there was no difference in RSDI, CSS, and SF-36 scores in CRS patients with or without NP. Importantly, in both nonrandomized cohorts, MT resection was associated with greater disease burden preoperatively, assessed by endoscopy, CT, olfaction testing, and symptom surveys.…”
Section: Xd3 Surgical Principles/techniques-mt Preservation or Resmentioning
confidence: 99%
“…1193,1194 Two additional studies have shown a beneficial effect on olfaction following MT resection. 1184,1195 Based on these studies, it appears the concern that MT resection reduces olfactory ability is unwarranted, and partial MT resection may in fact be associated with improved olfactory outcomes.…”
Section: Xd3 Surgical Principles/techniques-mt Preservation or Resmentioning
confidence: 99%
“…Soler ve ark. [20] kronik sinüzit nedeniyle endoskopik sinüs cerrahisi uyguladık-ları 242 hastayı kapsayan prospektif çalışmada iki taraflı orta konka rezeksiyonu yaptıkları 47 olguyu orta konkaya herhangi bir müdahale yapmadıkları 195 olgu ile koku fonksiyonları açısından kıyaslamış; koku identifikasyon testiyle değerlendirdikleri ameliyat sonrası koku fonksiyonlarının iki taraflı orta konka rezeksiyonu yapılan grupta daha iyi olduğunu bildirmişlerdir. Leopold [21] SİT (smell identifikasyon test) ve OCM (Odorant Confusion Matrix testi) ile orta konka rezeksiyonunun septum ile orta konka arasında nazal boşluğu artırdığını ve böylece koku molleküllerinin olfaktör epitele daha kolay ulaşmasını sağladığını ifade etmiştir.…”
Section: Discussionunclassified
“…Olfactory fibers descend from the olfactory cleft onto the superior turbinate and septum and occupy a space between 2 and 10 cm. 2,5 The incidence of postoperative hyposmia has been studied in various circumstances and using various techniques, including removal of the inferior portion of the superior turbinate, 6 removing the middle turbinate entirely or in part, 7,8 and also when septal deviation is corrected. 9,10 In all circumstances, the incidence is low and may be related either to the removal of olfactory neuroepithelium or by altering the flow of air.…”
Section: Middle Turbinatementioning
confidence: 99%